Persepsi Masyarakat terhadap Kinerja Pegawai di Kantor Kecamatan Marusu Kabupaten Maros - Andi Nuryadin; Andi Hendra Syam; A.Fadel Muhammad (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
Public Perception of Employee Performance at the Marusu District Office, Maros Regency. STIM-LPI Makassar Management Science Study Program Thesis (supervised by Dr. Andi Nuryadin S.E., M.Si. and Dr. Andi Hendra Syam, S.E., M.Si.). This research aims to determine the public's perception of the quality of public services at the Marusu District office, Maros Regency, which until now has not been known, regarding service procedures, certainty of completion time, completeness of facilities and infrastructure, employee behavior, and comfort. This research is a qualitative descriptive research with Respondents consisted of community leaders, youth leaders, religious leaders and women leaders as well as sub-district leaders. Data collection was carried out using observation, interviews and documentation techniques. The data analysis technique used is an interactive analysis technique including data collection, data reduction, data presentation, then drawing conclusions. The results of this research show that the public's perception of service users at the Marusu sub-district office, Maros Regency, is that aspects of public service procedures are easy to access, aspects of facilities and infrastructure are still lacking. Improving the provision of public services in Marusu sub-district, Maros district still depends on the number of queues and the public's perception of friendliness, politeness and comfort is considered good.